Lithium‐Metal Batteries via Suppressing Li Dendrite Growth and Improving Coulombic Efficiency. Issue 10 (8th September 2022) - Su, Laisuo; Manthiram, Arumugam
Abstract : Lithium‐metal batteries (LMB) are recognized as one of the most promising candidates for the next generation of batteries due to their high energy density. Extensive studies have been refocused on the field in the past decade to make the technology commercially viable. Despite exciting progress that has been made, the practical application of LMBs is still hampered by the uncontrollable Li plating morphology and inferior Coulombic efficiency (CE) during cycling. Herein, first, the relevant research that has been carried out in the past decade (2010–2021) is briefly summarized and then the Li plating behaviors, mechanistic understanding of these behaviors, and strategies to suppress Li dendrite growth are discussed. Finally, the methods and techniques to improve Coulombic efficiency (CE) is discussed, especially the design of liquid electrolytes, and possible research directions for the future development of LMBs. Abstract : This review summarizes the strategies for developing lithium‐metal batteries by suppressing Li dendrite growth and increasing Li Coulombic efficiency, including design of anode substrate, building artificial solid electrolyte interphase, engineering separator, developing advanced electrolyte, and controlling operating conditions. The mechanisms of Li dendrite growth and future research directions are also discussed.